Long-Read- and Short-Read-Based Whole-Genome Sequencing Reveals the Antibiotic Resistance Pattern of Helicobacter pylori - Limiao Hu; Xi Zeng; Qi Ai; Caijuan Liu; Xiaotuan Zhang; Yajun Chen; Logen Liu; Guo-Qing Li (Microbiology Spectrum, 2023)
ABSTRACT The rates of antibiotic resistance of Helicobacter pylori are increasing, and the patterns of resistance are region and population specific. Here, we elucidated the antibiotic resistance pattern of H. pylori in a single center in China and compared short-read- and long-read-based whole-genome sequencing for identifying the genotypes. Resistance rates of 38.5%, 61.5%, 27.9%, and 13.5% against clarithromycin, metronidazole, levofloxacin, and amoxicillin were determined, respectively, while no strain was resistant to tetracycline or furazolidone. Single nucleotide variations (SNVs) in the 23S rRNA and GyrA/B genes revealed by Illumina short-read sequencing showed good diagnostic abilities for clarithromycin and levofloxacin resistance, respectively. Nanopore long-read sequencing also showed a good efficiency in elucidating SNVs in the 23S rRNA gene and, thus, a good ability to detect clarithromycin resistance. The two technologies displayed good consistency in discovering SNVs and shared 76% of SNVs detected in the rRNA gene. Taking Sanger sequencing as the gold standard, Illumina short-read sequencing showed a slightly higher accuracy for discovering SNVs than Nanopore sequencing. There are two copies of the rRNA gene in the genome of H. pylori, and we found that the two copies were not the same in at least 26% of the strains tested, indicating their heterozygous status. Especially, three strains harboring a 2143G/A heterozygous status in the 23S rRNA gene, which is the most important site for clarithromycin resistance, were found. In conclusion, our results provide evidence for an empirical first-line treatment for H. pylori eradication in clinical settings. Moreover, we show that Nanopore sequencing is a potential tool for predicting clarithromycin resistance. IMPORTANCE Helicobacter pylori resistance has been increasing in recent years. The resistance profile, which is important for empirical treatment, is region and population specific. We found high rates of resistance to metronidazole, clarithromycin, and levofloxacin in H. pylori in our center, while no resistance to tetracycline or furazolidone was found. These results provide a reference for local physicians prescribing antibiotics for H. pylori eradication. Nanopore sequencing recently appeared to be a promising technology for elucidating whole-genome sequences, which generates long sequencing reads and is time-efficient and portable. However, a relatively higher error rate of sequencing reads was also found. In this study, we compared Nanopore sequencing and Illumina sequencing for revealing single nucleotide variations in the 23S rRNA gene, which determines clarithromycin resistance, and we found that although there were a few false discoveries, Nanopore sequencing showed good consistency with Illumina sequencing, indicating that it is a potential tool for predicting clarithromycin resistance.